1986
DOI: 10.1200/jco.1986.4.12.1851
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of spinal cord compression in kidney cancer.

Abstract: Forty-three patients with renal-cell carcinoma underwent treatment for spinal cord compression over a 7-year period. Of these, 32 patients underwent surgery, while 11 patients underwent radiation alone. Before operation, 25 patients had relapsed following prior radiation, while seven others received postoperative radiation. A more aggressive surgical approach, tailored to the site of compression within the spinal canal, was used with the majority undergoing gross total tumor resection by an anterior approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 26 publications
3
39
0
Order By: Relevance
“…The inferior margin of the cage is positioned ®rst, and the superior margin is impacted into place with gentle distraction of the interspace at 2 years while none of those treated with radiotherapy alone survived two years. 16,32 70% of surgical patients had signi®cant neurologic improvement compared to 45% of radiated patients. Other authors have reported survival rates of 30% or more at ®ve years following aggressive resection of solitary renal metastases.…”
Section: Discussionmentioning
confidence: 98%
“…The inferior margin of the cage is positioned ®rst, and the superior margin is impacted into place with gentle distraction of the interspace at 2 years while none of those treated with radiotherapy alone survived two years. 16,32 70% of surgical patients had signi®cant neurologic improvement compared to 45% of radiated patients. Other authors have reported survival rates of 30% or more at ®ve years following aggressive resection of solitary renal metastases.…”
Section: Discussionmentioning
confidence: 98%
“…6,18 Further study has focused specifically on the role of spinal SRS in the treatment of RCC metastasis to the spine, the promise of more therapeutic radiation dosing holding particular promise in the treatment of what was traditionally considered a radioresistant histology. 5,17,20,22,23 RCC metastases often progress despite EBRT, sometimes necessitating surgical intervention. Surgical management of RCC metastases, however, is associated with higher complication rates than the management of lesions of other, less hemorrhagic histological types.…”
Section: Discussionmentioning
confidence: 99%
“…9,15 Pertinently, RCC is historically considered a radioresistant tumor, particularly in the setting of EBRT. 5,17,20,22,23 Even in the setting of spinal SRS, Gerszten et al noted lower overall radiographic tumor control of RCC lesions in comparison with other histologies. 11 Nevertheless, several series have demonstrated the clinical efficacy of spinal SRS in treating radioresistant RCC lesions and elucidated factors that may contribute to treatment failure.…”
mentioning
confidence: 99%
“…Among these, only nine patients (7.4%) suffered postoperative wound-related complications. Five studies reported no complications (7,21,24,(28)(29)(30)35,38). Among these eight, only studies by Young et al (38) and Laohacharoensombat et al (35) reported the surgery-radiotherapy interval, which was 7 and 14 days, respectively.…”
Section: Evaluation Of the Datamentioning
confidence: 99%
“…The relationship was significant in four studies, but did not reach statistical significance in four others. From 15 studies we were able to extract information on 309 previously irradiated patients that were treated surgically, with wound complication rates of 11-50% (2,7,8,10,14,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Evaluation Of the Datamentioning
confidence: 99%